2007
DOI: 10.1097/ajp.0b013e318074c95c
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Local Anesthetic Plus Corticosteroid for the Treatment of Cervical Brachial Radicular Pain: Single Injection Versus Continuous Infusion

Abstract: Therapy with continuous epidural local anesthetic and methylprednisolone provides better control of chronic cervicobrachial pain compared with Single injection. These results are discussed with respect to the possible mechanism of action of the drugs and may relate to the physiopathologic mechanisms associated with neuronal plasticity that result in chronic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
149
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(152 citation statements)
references
References 45 publications
1
149
0
1
Order By: Relevance
“…37 Furthermore local anesthetic agents can also exert beneficial effects by curtailing pain-induced neuronal sensitization and release of neurotransmitters involved in pain pathways. [38][39][40][41] Alternately, administration of corticosteroids in the epidural space is thought to reduce inflammatory edema of the injured nerve root, 42 decrease sensitization of the dorsal horn neurons, 43 and suppress the transmission of nociceptive C fibres. 44 In clinical practice, both agents are often combined.…”
Section: Epidural Blockadementioning
confidence: 99%
“…37 Furthermore local anesthetic agents can also exert beneficial effects by curtailing pain-induced neuronal sensitization and release of neurotransmitters involved in pain pathways. [38][39][40][41] Alternately, administration of corticosteroids in the epidural space is thought to reduce inflammatory edema of the injured nerve root, 42 decrease sensitization of the dorsal horn neurons, 43 and suppress the transmission of nociceptive C fibres. 44 In clinical practice, both agents are often combined.…”
Section: Epidural Blockadementioning
confidence: 99%
“…In general, cervical epidural injections are not recommended for axial neck pain, but they are considered to be reasonable for disc herniation with radiculitis and spinal stenosis 6,10-14,16-18,35-37. A single report of a one year follow-up of discogenic neck pain after excluding cervical facet joint pain in 120 patients without disc herniation or radiculitis showed a primary outcome of significant pain relief and improvement in functional status (≥ 50%) in 72% of patients in Group I receiving local anesthetic and 68% in Group II receiving local anesthetic and steroids.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of levator scapulae syndrome is attributed to the excitement of the free nerve endings inside the muscle fascia. Recently, studies have reported that interfacial block, relieved myofascial pain by reducing the excitability of these nerve endings [10][11][12].…”
Section: Discussionmentioning
confidence: 99%